NAVIGATING EMERGENCY REMOTE TEACHING: UNDERSTANDING PRESENT NEEDS AND ANTICIPATING FUTURE DIGITAL COMPETENCE IN HIGHER EDUCATION (International Journal of Food and Nutritional Sciences, 2022)
Online and hybrid learning environments are becoming more and more common in higher education. The integration of digital tools and competencies is seen as crucial, guided by institutional policies and frameworks for digital competence. In reaction to the COVID-19 pandemic, emergency remote teaching (ERT) became more popular, necessitating the deployment and maintenance of digital competencies. Throughout this time, researchers documented a variety of remote teaching strategies used in higher education, demonstrating how flexible educators can be even in the face of little preparation. In order to create a conceptual framework for ERT digital competence, this study examined empirical ERT research over the previous two years. The conceptual framework was then used as a lens through which to examine teaching or digital competency frameworks from Australian institutions. The results of this study show that digital capabilities pertinent to ERT were captured in a variety of ways via prepandemic instruction and digital competence frameworks. From a practical standpoint, the results provide a foundation for comprehending the digital competencies required by ERT to guarantee readiness in the event of a crisis that interrupts educational services.